A comprehensive understanding of grain selection in spiral grain selector during directional solidification. (10th March 2022) - Wang, Binqiang; Zeng, Long; Ren, Neng; Xia, Mingxu; Li, Jianguo
Highlights: The grain selection in spiral selector is a coupling process where high order dendrites branch in the front side and primary dendrites disappear in the back side. And it is influenced by a combination effect of "space expansion mechanism", "geometrical restriction mechanism" and "competitive grain growth". The smaller of the take off angle (θ) is, the larger space and the stronger driving force high order dendrites will get, and the higher efficiency the selector will be Grain with preferred secondary dendrites instead of preferred primary dendrites could outcompete during grain selection, and this is the reason why spiral grain selector cannot optimize the orientation of the primary dendrites. Abstract: It is of great importance to further investigate grain selection mechanism for the production of single crystal (SX) turbine blade because a single crystal with optimized crystal orientation will enhance service performance of the blade severely. In this paper, single crystals with different deviation angles, i.e. 6°, 12° and 29°, were obtained using directional solidification under the same casting conditions. It has been found that the grain selection in spiral selector is a coupling process where high order dendrites branch in the front side and primary dendrites disappear in the back side based on the metallographic analysis and electron back scatter diffraction (EBSD). Considering the development of liquid/solid interface by numerical simulation, a combination effect with space expansion, geometrical restriction and grain competition was proposed for spiral grain selection. The space expansion mechanism dominates the process as it provides growth space and driving force for high order dendrites advancing. Thereby, the smaller the take-off angle ( θ ) is, the larger space and the stronger driving force high order dendrites will get, and the higher efficient the selector will be. The competitive growth between the secondary dendrites plays more contribution than that of primary dendrites, i.e. grain with preferred secondary dendrites instead of preferred primary dendrites could outcompete during grain selection, and this is the reason why spiral grain selector cannot optimize the orientation of the primary dendrites. These findings provide experimental evidence for spatial control of SX growth, and benefit the sophistic casting fields such as turbine blade casting for improved yield.